Menopausal hormone therapy use and risk of primary liver cancer in the clinical practice research datalink. Issue 9 (31st December 2015) - McGlynn, Katherine A.; Hagberg, Katrina; Chen, Jie; Braunlin, Megan; Graubard, Barry I.; Suneja, Neha; Jick, Susan; Sahasrabuddhe, Vikrant V.
Abstract : Primary liver cancer occurs less commonly among women than men in almost all countries. This discrepancy has suggested that hormone levels and/or exogenous hormone use could have an effect on risk, although prior studies have reached inconsistent conclusions. Thus, the current study was conducted to examine the relationship between menopausal hormone therapy (MHT) use and development of liver cancer. A nested case‐control study was conducted within the United Kingdom's Clinical Practice Research Datalink (CPRD). Controls were matched, at a 4‐to‐1 ratio, to women diagnosed with primary liver cancer between 1988 and 2011. A second match, based on whether the cases and controls had diabetes, was also conducted. Odds ratios (OR) and 95% confidence intervals (95%CI) for associations of MHT with liver cancer were estimated using conditional logistic regression adjusted for known risk factors. In the overall match, 339 women with liver cancer were matched to 1318 controls. MHT use was associated with a significantly lower risk of liver cancer (ORadj = 0.58, 95%CI = 0.37–0.90) especially among users of estrogen‐only MHT (ORadj = 0.44, 95%CI = 0.22–0.88) and among past users (ORadj = 0.53, 95%CI = 0.32–0.88). Among the matched cases ( n = 58) and controls ( n = 232) with diabetes, the odds ratios were similar to the overall analysis (ORadj = 0.57, 95%CI = 0.09–3.53), but did not attain statistical significance. In the current study, MHT use, especially estrogen‐only MHT use, was associated with a significantly lower risk of liver cancer. These results support the need of further investigation into whether hormonal etiologies can explain the variation in liver cancer incidence between men and women. Abstract : What's new? Pronounced gender discrepancy in the risk of primary liver cancer suggests that steroid hormone levels or exogenous hormone use are related to risk. In this analysis of data from the Clinical Practice Research Datalink in the United Kingdom, risk of liver cancer was found to be significantly reduced among women on menopausal hormone therapy (MHT). The association was evident particularly among users of estrogen‐only MHT. The findings suggest that exogenous hormones protect against liver cancer, a phenomenon inviting further investigation.